2020
DOI: 10.1177/1049732320951145
|View full text |Cite
|
Sign up to set email alerts
|

Gratitude in Health Care: A Meta-narrative Review

Abstract: Research into gratitude as a significant sociological and psychological phenomenon has proliferated in the past two decades. However, there is little consensus on how it should be conceptualized or investigated empirically. We present a meta-narrative review that focuses on gratitude in health care, with an emphasis on research exploring interpersonal experiences in the context of care provision. Six meta-narratives from literatures across the humanities, sciences, and medicine are identified, contextualized, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
58
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(61 citation statements)
references
References 78 publications
3
58
0
Order By: Relevance
“…Gratitude is inherent in vulnerable human beings and all participants expressed expressions of gratitude to the professionals and health system and for the medical treatment received [35]. Something similar was reflected in the study by Niner et al on the birth experiences in Australia of Karen and Kayin women displaced from Burma [36].…”
Section: Discussionsupporting
confidence: 52%
“…Gratitude is inherent in vulnerable human beings and all participants expressed expressions of gratitude to the professionals and health system and for the medical treatment received [35]. Something similar was reflected in the study by Niner et al on the birth experiences in Australia of Karen and Kayin women displaced from Burma [36].…”
Section: Discussionsupporting
confidence: 52%
“…It also was a direct indication that they were doing a good job as nurses. As Day et al [ 42 ] note, gratitude is important in enhancing nurses’ worklife and caregiving relationships. For retired nurses in rural and remote communities, gratitude is as important to have from the community as it is from the workplace.…”
Section: Discussionmentioning
confidence: 99%
“…Our recent meta‐narrative review of gratitude in healthcare identified a need for research on the ways in which gratitude acquires meaning in real‐world situations. 13 Yoshimura and Berzins 14 have called for a focus on expressions of gratitude to extend and enrich the plethora of research on gratitude experiences. In particular, they call for examinations of the semantic features of gratitude expressions and the topics on which people focus when thanking others.…”
Section: Introductionmentioning
confidence: 99%